2002
DOI: 10.1029/2002ja009272
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceleration in the ionospheric Alfven resonator

Abstract: [1] FAST wave and particle observations on the nightside polar cap boundary indicate the operation of the ionospheric Alfven resonator (IAR). Large impulsive electric and magnetic field deviations on the boundary between the auroral oval and the polar cap close to magnetic midnight are correlated with accelerated electrons and excite semi periodic oscillations with a frequency of $0.5 Hz. Linear one-dimensional simulations of the Alfven resonator including parallel electric fields due to electron inertial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
121
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 38 publications
15
121
0
1
Order By: Relevance
“…It should be recognized that if this is the case, the visible aurora would not necessarily be on the same field lines as those containing the fast flow, as is sometimes assumed. This statement is also consistent with the observations from FAST that the poleward boundary region of the aurora is frequently characterized by broadband electron acceleration [Chaston et al, 2002b].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It should be recognized that if this is the case, the visible aurora would not necessarily be on the same field lines as those containing the fast flow, as is sometimes assumed. This statement is also consistent with the observations from FAST that the poleward boundary region of the aurora is frequently characterized by broadband electron acceleration [Chaston et al, 2002b].…”
Section: Discussionsupporting
confidence: 80%
“…However, the FAST spacecraft [e.g., Chaston et al, 2000Chaston et al, , 2002aChaston et al, , 2003Chaston et al, , 2006Chaston et al, , 2007 has observed these broadband distributions in conjunction with Alfvénic fluctuations, suggesting that these electrons are accelerated by parallel electric fields in kinetic Alfvén waves. This conclusion was supported by models for the Alfvén wave acceleration of these electrons [e.g., Kletzing, 1994;Thompson and Lysak, 1996;Chaston et al, 1999Chaston et al, , 2000Chaston et al, , 2002aChaston et al, , 2002bKletzing and Hu, 2001;Lysak and Song, 2003a, 2003b, which gave results consistent with observation. Thus, such events have been termed the "Alfvénic aurora.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Specific spectral resonance structures measured on the ground have been considered evidence for IAR phenomena [Belyaev et al, 1990]. Subsequent in situ measurements have expanded our knowledge of IAR dynamics [Grzesiak, 2000;Chaston et al, 2002;Bösinger et al, 2004;Parent et al, 2010]. In addition to intrinsic spectral structures, the main characteristics of IAR shear Alfvén waves at high latitude include a wave vector in the parallel direction and oscillations of the electric and magnetic fields perpendicular to the geomagnetic field.…”
Section: Ionospheric Alfvén Resonatormentioning
confidence: 99%
“…Transversely accelerated hydrogen and oxygen ions of tens to a few hundred eV suggest the existence of even shorter transverse scales of the wavefield. Fortunately, there is plenty of evidence of smaller-scale components in the electric as well as magnetic fields [e.g., Stasiewicz et al, 1997;Chaston et al, 2002]. They are probably not impressed from the generator but may rather be a secondary product of the interaction of the incoming wider wave with the ionospheric resonator by multiple reflections with periods in the 1 Hz range [Stasiewicz et al, 1997;Chaston et al, 2002;Lysak and Song, 2002].…”
Section: Alfvénic Arcs/onset Arcsmentioning
confidence: 99%